Penggunaan Media Sosial Sebagai Double Edge Sword dalam Membentuk Literasi Keagamaan Siswa Madrasah Aliyah - Salmi Wati; Eliwatis Eliwatis; Muaddyl Akhyar (IAIN Batusangkar, 2025)
This study aims to explore how social media can be utilized to enhance students' religious understanding in Madrasah Aliyah, with a focus on fiqh and aqidah-akhlak. The research employs a qualitative method with a case study approach, using interviews, observations, and documentation as data collection techniques. The findings indicate that social media, despite its risk of misinformation, can serve as an effective learning tool when wisely utilized by teachers. These findings contribute significantly to the development of digital religious literacy, offering recommendations for educators to guide students in filtering valid religious information. This study also opens opportunities for further research on the long-term impact of social media use in religious education.